Bridging Socio-Economic and Cultural Fissures: A Case Study on Critical Infrastructure in Rural Karnataka of India (Global Business Management Review (GBMR), 2022)
Critical infrastructure entails assets essential for the survival of a society and economy1. In the rural context, the most commonly associated with the term are facilities for electricity generation, transmission and distribution; transport and distribution; drinking water supply and sewerage; agriculture, food production and distribution; public health; connectivity; financial services and social, cultural and traditional composure. This vision of critical infrastructure has impelled many a governments nationally as well as internationally to extend such facilities up to the grass-root level. With a view to support state governments, in this backdrop, Government of India, in FY1995, created the Rural Infrastructure Development Fund (RIDF) for completing incomplete rural projects in various sectors. It is anticipated that the financial support provided under this Fund would accelerate the rate of capital formation, as also, add steadily to the flow of output and employment opportunities in the rural areas of the country. At the time of launching of RIDF, the State Governments were experiencing a severe resource crunch over the years on the one hand and the banks, particularly the commercial banks, on the other, we're unable to comply with the priority sector lending norms stipulated by the Reserve Bank of India. It was therefore realized in FY1995 that the shortfall in the priority sector norms be pooled in the forms of deposits for raising the Fund to support the incomplete infrastructure projects of various state governments. The corpus towards the fund was to be initially contributed by scheduled commercial banks, excluding foreign banks, to the extent of their shortfall against the targets in agricultural lending, subject to a ceiling of 1.5 per cent. However, from fifteen series onwards, the allocation of Fund is being met out of shortfall from priority sector and /or agriculture and/or weaker section. Over the years, the corpus has increased from INR200 million in the first series to INR2000 million in eighteen series2. Rural connectivity and minor irrigation sectors had a major share of investment from the Fund at all-India level. Furthermore, rural connectivity in general and construction of bridges in rural area in particular do have socio-economic implications, as also, environmental and ecological issues, in the daily life of the rural masses. This case study therefore invites the attention of all including the central governments in furthering the noble cause of developing the infrastructure for the rural masses.